2021
DOI: 10.1007/s00423-021-02214-9
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic herniation after esophagogastric surgery: systematic review and meta-analysis

Abstract: Introduction The anatomy of the esophageal hiatus is altered during esophagogastric surgery with an increased risk of postoperative hiatus hernia (HH). The purpose of this article was to examine the current evidence on the surgical management and outcomes associated with HH after esophagogastric surgery for cancer. Materials and methods Systematic review and meta-analysis. Web of Science, PubMed, and EMBASE data sets were consulted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…This meta-analysis also included 99 patients with post-esophagectomy hiatal hernia who were asymptomatic, of whom 17 were electively repaired [3]. Some studies have reported a higher incidence of hiatal hernia in minimally invasive esophagectomy as compared to open surgery [1,4]. Kent et al in their study of 1075 esophagectomies had an incidence of 0.8 % in open cases vs. 2.8% in minimally invasive cases with an overall incidence of 1.86% [5].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This meta-analysis also included 99 patients with post-esophagectomy hiatal hernia who were asymptomatic, of whom 17 were electively repaired [3]. Some studies have reported a higher incidence of hiatal hernia in minimally invasive esophagectomy as compared to open surgery [1,4]. Kent et al in their study of 1075 esophagectomies had an incidence of 0.8 % in open cases vs. 2.8% in minimally invasive cases with an overall incidence of 1.86% [5].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of hiatal hernia post-esophagectomy is variable and ranges from 0.4% to 15% [ 1 ]. A meta-analysis by Bona et al showed the post-esophagogastric surgery prevalence of hiatal hernia to be 3.18%, with 2.01% requiring surgery [ 1 ]. In our retrospective analysis of past 4 years, we have also found the hiatal hernia rates to be around 3%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations